IMPLEMENTASI MODEL TEMATIK DALAM PEMBELAJARAN AGAMA ISLAM PADA PENDIDIKAN ANAK USIA DINI DI RAUDHATUL ATHFAL AL-JIHAD - Masdalipah, Masdalipah; Mujahidin, Endin; Bahruddin, Ending (Ta’dibuna: Jurnal Pendidikan Islam, 2017)
Implementation of early childhood education (ECD) in Indonesia, especially under the auspices of Islamic educational institutions are still very limited and have not been able to cater to the educational needs of early children across Indonesia. In addition, an increase in the quantity of early childhood institutions, has not been accompanied by an increase in quality. For that, we need innovative learning model in early childhood institutions. This research focuses on the implementation of thematic learning model on Islamic Education in Raudhatulathfal Al-Jihad, which covers all aspects of planning (program), execution (process), evaluation of thematic learning, and its impact on the quality of Islamic education. The research method used was eksperimental research. In addition to testing, the researcher also collected qualitative data through observation and interviews. The study is located in the Kelurahan Kalibaru RT.02 RW.02 Kecamatan Cilodong, Depok, West Java. Formally, the tryout of study was conducted from January to July 2012. Based on the research conducted, through validation readability level, student responses and learning outcomes, the thematic learning model on Islamic education deserves to be applied to early childhood education in Raudhatulathfal Al-Jihad and also applied to other institutions those are similar. In the pre-test results, two different groups obtained about average 7.737 for the experimental group; and 7.789 for the controlled group. Once the thematic learning model on Islamic education applied, then the group of students performed post-test, the result is 8.578 for the experimental group; and 7.947 for the controlled group. The impact of the implementation of the model thematic learning on Islamic education in early childhood toward the quality of Islamic education is very significant. This is obvious from the responses of students very well, that is 96.51%, and the learning outcomes achieved 100% completion. Through a thematic learning model on Islamic education in early childhood, the average increase in the quality of education obtained in the experimental group were higher (0.841) than the controlled one (0.158). Therefore, it is highly recommended that thematic model of learning to be applied in Islamic educational institutions which organizing early childhood education with specific instructional objectives for learning Islamic Education, which covers three areas; cognitive, affective and psychomotor, so that every student in early childhood education can develop basic competencies, such as morals behavioral/social emotional, Islamic competence and other basic competences as the provision they entered to the next educational level.